Analysis of Road and Drainage Project Performance Control Using the Earned Value Method: A Case Study of Road and Drainage Work Row 46 Segment II Jakarta Garden City - Agus Sasmita (Eduvest - Journal of Universal Studies, 2025)
Construction project control is very important to achieve project performance in accordance with the plan that has been set and is essential to implement, especially in relation to cost, quality, and time. The methods commonly used to carry out control are the Conventional Cost Management Method and the Earned Value Method, where both methods share the same goal: to control project performance so that the project is executed according to the plan. The purpose of this study is to evaluate and analyze the performance of the Road and Drainage Project in Row 46 Segment II, Jakarta Garden City, by applying both the Conventional Cost Management Method and the Earned Value Method (EVM). Using a descriptive research approach, primary and secondary data were collected through field surveys, documentation, and project reports over a sixteen-week period. The findings reveal that in week 7, the project was ahead of schedule (schedule underrun) but incurred higher costs (cost overrun), whereas by week 16, delays (schedule overrun) were observed alongside continued cost overruns. EVM demonstrated superior capability in monitoring deviations and forecasting final project costs and completion timelines through indicators such as SPI and CPI. The research concludes that EVM offers a more dynamic and precise tool for project control, enabling timely corrective measures and improved decision-making compared to conventional approaches.